A delicate balance : constructing a conservation culture in the South Carolina lowcountry - Halfacre, Angela C. (University of South Carolina Press, 2012)
Sustainability of the natural environment and of our society has become one of the most urgent challenges facing modern Americans. Communities across the country are seeking a viable pattern of growth that promotes prosperity, protects the environment, and preserves the distinctive quality of life and cultural heritage of their regions. The coastal zone of South Carolina is one of the most endangered, culturally complex regions in the state and perhaps in all of the American South. A Delicate Balance examines how a multilayered culture of environmental conservation and sustainable development.